2017
DOI: 10.5935/0103-507x.20170066
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of pediatric patients after discharge from the intensive care unit using the Functional Status Scale

Abstract: ObjectiveTo evaluate the functional status of pediatric patients after discharge from the pediatric intensive care unit using the Functional Status Scale and to compare the time of invasive mechanical ventilation, length of stay in the pediatric intensive care unit, and Pediatric Index of Mortality 2 results among individuals with different degrees of functional impairment.MethodsA cross-sectional study was conducted on patients who were discharged from a pediatric intensive care unit. The functional evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 16 publications
4
29
0
4
Order By: Relevance
“…( 18 ) For the present study, the outcome was analyzed in two distinct ways: we first grouped the scores into levels of dysfunction, i.e., no dysfunction (6 - 7), mild dysfunction (8 - 9), moderate dysfunction (10 - 15), severe dysfunction (16 - 21) and very severe dysfunction (> 21), a classification method used in previous studies. ( 14 , 15 ) Secondly, we dichotomized functional status into adequate function/mild dysfunction and moderate/severe dysfunction.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…( 18 ) For the present study, the outcome was analyzed in two distinct ways: we first grouped the scores into levels of dysfunction, i.e., no dysfunction (6 - 7), mild dysfunction (8 - 9), moderate dysfunction (10 - 15), severe dysfunction (16 - 21) and very severe dysfunction (> 21), a classification method used in previous studies. ( 14 , 15 ) Secondly, we dichotomized functional status into adequate function/mild dysfunction and moderate/severe dysfunction.…”
Section: Methodsmentioning
confidence: 99%
“…Interventions performed during hospitalization ( 12 - 14 ) can cause deficits in the overall functional status of children. ( 3 , 14 - 16 ) Studies have shown that functional decline is directly influenced by clinical variables ( 3 , 17 ) and by risks inherent to the medical intervention and the underlying disease. ( 15 )…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations